2022
DOI: 10.3390/ma15144874
|View full text |Cite
|
Sign up to set email alerts
|

Stain Susceptibility of Composite Resins: Pigment Penetration Analysis

Abstract: Composite resins are considered the material of choice for esthetic direct restorations, considering both their satisfying esthetic and mechanical properties. The success of composite resin restorations depends highly on their color stability. Discoloration causes color mismatch, consequent patient dissatisfaction, and eventually additional costs for correction/replacement of the restoration. The purpose of this study was to evaluate the degree of pigment penetration within the composite resins, in order to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Recent studies showed that the penetration of water and pigments was higher in nanohybrid composite resin than in microhybrid composite resin, which was attributed to a lack of complete silanization of nanoparticle clusters and prepolymerized fillers in nanohybrid composite resin. These properties are also seen in Grandio composite resin [24][25][26]. In addition, some researchers have reported that an increase in the size of filler particles increases the composite resin's color stability by decreasing the ratio of the organic filler matrix [26,27].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies showed that the penetration of water and pigments was higher in nanohybrid composite resin than in microhybrid composite resin, which was attributed to a lack of complete silanization of nanoparticle clusters and prepolymerized fillers in nanohybrid composite resin. These properties are also seen in Grandio composite resin [24][25][26]. In addition, some researchers have reported that an increase in the size of filler particles increases the composite resin's color stability by decreasing the ratio of the organic filler matrix [26,27].…”
Section: Discussionmentioning
confidence: 88%
“…Although the present study collected important data on the effects of laser, Sof-Lex discs, and bleaching agents on removing stains from composite resin surfaces. The discoloring solution in the present study (coffee) does not represent all the solutions the teeth might be exposed to clinically [24].…”
Section: Discussionmentioning
confidence: 99%
“…They stated that it could be due to the composition of the resin matrix and the porosity of the nanoclusters and glass fillers. Cinelli et al [ 24 ] concluded that the particles of the nanoclusters are not individually silanized and resulted in more water and pigment infiltration in nanohybrid composite resins.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of composite material used for dental restorations is another factor that can influence their aesthetic stability. Different composite materials vary in their susceptibility to color changes, making material selection a crucial consideration when planning treatments for patients who smoke 12 .…”
Section: Introductionmentioning
confidence: 99%